Genotyping of Cryptosporidium species in children suffering from diarrhea in Sharkyia Governorate, Egypt - Samira Metwally Mohammad; Magda Saad Ali; Sara Ahmed Abdel-Rahman; Raghda Abdelrahman Moustafa; Mohamed Hassan Sarhan (Journal of Infection in Developing Countries)
Introduction: The protozoan parasite Cryptosporidium is one of the principal reasons for childhood diarrhea around the world. This work aimed to differentiate Cryptosporidium species among children suffering from diarrhea in Sharkyia Governorate, Egypt.